2015
DOI: 10.1016/j.neulet.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter polymorphisms predict response inhibition in healthy volunteers

Abstract: Serotoninergic transmission is reliably implicated in inhibitory control processes. The aim of this study was to test the hypothesis if serotonin transporter polymorphisms mediate inhibitory control in healthy people. 141 healthy subjects, carefully screened for previous and current psychopathology, were genotyped for the 5-HTTLPR and rs25531 polymorphisms. Inhibitory control was ascertained with the Stop Signal Task (SST) from the Cambridge Neuropsychological Test Automated Battery (CANTAB). The triallelic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Indeed, changes in inhibitory control performance linked to alternations in DA function within the striatum (Buckholtz et al, 2010; Neill, 1976; Pattij et al, 2014) the NAcc (Cardinal et al, 2001; Sabol et al, 2000), and the hippocampus (Abela et al, 2013) have been reported. Alterations within other monoamine systems including serotonin (Fletcher et al, 2009; Landrø et al, 2015) and norepinephrine (Bari & Robbins, 2013; Logemann et al, 2013) have also been shown to affect inhibitory control performance. PFC neurons projecting to monoamine cell bodies in the brain stem (Robbins & Arnsten, 2009) and the NAcc (Leggio et al, 2009) appear to play a neuromodulatory role by recruiting other necessary monoamine systems when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in inhibitory control performance linked to alternations in DA function within the striatum (Buckholtz et al, 2010; Neill, 1976; Pattij et al, 2014) the NAcc (Cardinal et al, 2001; Sabol et al, 2000), and the hippocampus (Abela et al, 2013) have been reported. Alterations within other monoamine systems including serotonin (Fletcher et al, 2009; Landrø et al, 2015) and norepinephrine (Bari & Robbins, 2013; Logemann et al, 2013) have also been shown to affect inhibitory control performance. PFC neurons projecting to monoamine cell bodies in the brain stem (Robbins & Arnsten, 2009) and the NAcc (Leggio et al, 2009) appear to play a neuromodulatory role by recruiting other necessary monoamine systems when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Gene variants in the dopamine and serotonin neurotransmission system have been reported to contribute to interindividual differences in response inhibition and its neural correlates (Baehne and others 2009; Braet and others 2011; Congdon and others 2009; Congdon and others 2008; Cornish and others 2005; Cummins and others 2012; Filbey and others 2012; Kramer and others 2009; Landro and others 2014; Mulligan and others 2014; Stoltenberg and others 2006; Swanson and others 2000). Two variable number tandem repeat (VNTR) polymorphisms, one found in the 3′untranslated region (3′UTR) of the dopamine transporter gene ( SLC6A3/DAT1 ) and the other in the exon 3 of the dopamine receptor D4 gene ( DRD4) , have been associated with decreased response inhibition performance (Congdon and others 2009; Congdon and others 2008; Cornish and others 2005; Filbey and others 2012; Mulligan and others 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Null-findings have also been reported (Colzato and others 2010; Heinzel and others 2013; Langley and others 2004; Rommelse and others 2008). Carriers of the short allele of the serotonin transporter ( SLC6A4/5-HTT) HTTLPR polymorphism were found to exhibit worse inhibitory control than those without this allele (Landro and others 2014). However, two smaller previous studies did not find an association between HTTLPR and inhibitory control (Clark and others 2005; Drueke and others 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective serotonin reuptake inhibitors (SSRIs), though efficacious in the treatment of OCD, have been unable to affect SST performance across a number of studies (51,56,70,75,81) with the exception of a beneficial effect of citalopram in Parkinson's disease (82). Subjects carrying a low expression variant of the serotonin transporter had poorer SST performance compared to high expression carriers (83), however, an earlier study failed to find any association between allelic variation in this serotonin transporter polymorphism and SST performance (84). The latter study also failed to find any effect of acute tryptophan depletion on SST performance, regardless of genotype (84), and in rodents serotonin L. Sanjay Nandam Page 20 of 62 depletion does not appear to affect SSRT (85).…”
Section: The Neuropharmacology Of Response Inhibitionmentioning
confidence: 99%